A expansão do ensino de Direito: massificação que desqualifica ou democratização a serviço da prática da justiça no Brasil? - Almeida Júnior, Fernando Frederico de (2006)
The intention of this work is to inquire if contradictions are penetrating the education of the Right in the country, to understand its process of mercantilism and technicality and to study the consequences that laborious education of the Right can generate, everything without forgetting that the combination between the society urban-industrial and the democratic State of Right, after 1988, increased the economic contradictions, social and typically capitalist politics and, therefore, increased the demands for the services named "operators of the law". It was analyzed, that, the existing relations between histories of Brazil, the Right and legal education, adopting a description-critical vision. The research presented initially gave brief considerations to the history of Brazil and its relation with the Right, discourse concerning the Portuguese magistrate of the colonial period and the graduate-jurist of XIX and XX centuries, as well as the subordination of the "operators of the law" to the interests of the hegemonic elites at each moment. It became, after that, a referring, data-collecting to all the implanted courses of the Right until the present, proceeding to an approach by geographic region and, inside of them, for an unit of the federacy, differentiating, still, the private institutions of the public. It was elaborated, at this moment, a brief case study on a public university. It was looked into, to identify the entities related with the education of the Right in the country and its legal and/or statutory attributions, also scoring the moments where such people can and/or must intervene with the creation and management of the institutions of superior education, as well as with which half are endowed with checking into these. The research continued with the study of the objectives of the education of the Right, looking to identify its real function in Brazil. History demonstrates that the State and the professionals of the Right in Brazil effectively had never been worried about the poverty, or the "forgotten", with the excluded ones, with the great mass of the population. They had always been protective of an elitist legalism that moved them away from the Brazilian historical reality, what has occurred until the present. The yearnings of the population for a life improvement, for more respect and dignity, had generated very elitist demand that attracted the private initiative for a market until then little explored and superior education. Consequence of this was the proliferation of the private superior courses in the country, also the courses of the Right. Such proliferation is imposed and must be accepted by the State and the professional organizations. To the State it only remains to check the quality of offered education. To the professional organizations its only charge is to select those that will be able to exert definitive professions. Both are hindered to restrict the opening of courses with foundations that disrespect the disposed in the Great Charter. The proliferation of the courses of the Right with certainty will increase the respect to the rights of the excluded and, therefore, it will improve the practical one of justice in the country. The opening of new courses of graduation for the Right and the subsequent increase of the possibility of more people to graduate in legal sciences, it constitutes a small step in direction to the practical one of justice in Brazil, to the reduction of the social inequalities and to the rise of the dignity for human being of the Brazilian.